Does medical students' gender affect their clinical learning of gynaecological examination? A retrospective cohort study. Issue 1112 (25th April 2018) - Wallbridge, Thomas; Holden, Angela; Picton, Aled; Gupta, Janesh
Abstract: Introduction: Medical graduates should be competent in gynaecological examination as well as associated skills including speculum use and swabbing. Male and female medical students may have different opportunities to practise these skills in clinical environments, potentially impacting on confidence and competence. This study explores this further via reviewing students' learning experience in genitourinary medicine (GUM) and obstetrics and gynaecology (O&G) clinics. Methods: Cross-sectional study of 759 year 4 and year 5 University of Birmingham medical students via an online questionnaire. This explored degree of participation, impact of gender and self-reported confidence. Results: Overall response rate was 31% (233/759). Students of either gender who observed an examination being performed by a clinician were more likely to perform the same examination. Female students reported more opportunities to practise gynaecological examination and associated skills. Female students were more likely to be granted consent to perform speculum examinations, vaginal swabbing and vaginal bimanual examinations. Sixty-five per cent of male students felt that their gender affected their learning experience with female patients. Despite this, there was no significant difference in self-reported confidence level in performing gynaecological examinations between genders at the end of placement. Conclusion: The majority of male students perceived that their gender impacted their clinical experience in O&G and GUM. Self-reported confidence levels were unaffected, which could reflect varying approaches to competence between genders. The link between observing examinations and subsequent opportunities to practise is key. This could demonstrate students developing rapport and trust with patients, and clinicians' roles as gatekeepers.